Distinctive Features of Taxation of Small Business and Private Entrepreneurship - Davlatbay, Kudbiyev (Journal of Sustainability in Integrated Policy and Practice, 2023)
This study is devoted to the study of the peculiarities of taxation of small businesses and private entrepreneurship. The study examines the tax policy pursued by the Republic of Uzbekistan in the field of state economic support for small businesses and private entrepreneurship, creating a favorable tax environment for them. The influence of tax reforms of recent years on the development of small business and private entrepreneurship is analyzed.